Recent advances of photodiagnosis and treatment for head and neck squamous cell carcinoma - Yining Zhang; Zhenfang Li; Chengchi Zhang; Chengying Shao; Yanting Duan; Guowan Zheng; Yu Cai; Minghua Ge; Jiajie Xu (Neoplasia: An International Journal for Oncology Research)
Head and neck squamous cell carcinoma (HNSCC) are the most common type of head and neck tumor that severely threatens human health due to its highly aggressive nature and susceptibility to distant metastasis. The diagnosis of HNSCC currently relies on biopsy and histopathological examination of suspicious lesions. However, the early mucosal changes are subtle and difficult to detect by conventional oral examination. As for treatment, surgery is still the primary treatment modality. Due to the complex anatomy and the lack of intraoperative modalities to accurately determine the incision margins, surgeons are in a dilemma between extensive tumor removal and improving the quality of patient survival. As more knowledge is gained about HNSCC, the increasing recognition of the value of optical imaging has been emphasized. Optical technology offers distinctive possibilities for early preoperative diagnosis, intraoperative real-time visualization of tumor margins, sentinel lymph node biopsies, phototherapy. Fluorescence imaging, narrow-band imaging, Raman spectroscopy, optical coherence tomography, hyperspectral imaging, and photoacoustic imaging have been reported for imaging HNSCC. This article provides a comprehensive overview of the fundamental principles and clinical applications of optical imaging in the diagnosis and treatment of HNSCC, focusing on identifying its strengths and limitations to facilitate advancements in this field.